The Anti Windup PID controller ISE tuning based for small-scale steam distillation system / Haslizamri Md Shariff … [et al.] - Md Shariff, Haslizamri; Rahiman, Mohd Hezri Fazalul; Adnan, Ramli; Marzaki, Mohd Hezri; Tajjudin, Mazidah; A. Jalil, Mohd Hafiz (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
Proportional-Integral-Derivative (PID)controller are easy to develop and tuned, efficient and reliable in any control system areas. The main problem of PID controller when a system facing unwanted windup phenomena due to existence of input saturation. This phenomenonis occur due to failure of controller to unwind the control input signal. The objective of this paper is to develop the Proportional-Integral-Derivative integrated AntiWindup (PIDAW) controllers in order to diminish windup phenomenon using the tracking calculation tuning by Integral Square Error (ISE). The simulation results show that the proposed PIDAW controller is capable to reduce the overshoot and faster settling time. It is proven that PIDAW controller has better performance compared to the conventional PID controller.